Be it ever so humble: Proposing a dual-dimension account and measurement of humility. Issue 1 (2nd January 2018) - Wright, Jennifer Cole; Nadelhoffer, Thomas; Thomson Ross, Lisa; Sinnott-Armstrong, Walter
Abstract: What does it mean to be humble? We argue that humility is an epistemically and ethically aligned state of awareness – the experience of ourselves as a small part of a larger universe and as one among a host of other morally relevant beings. So conceived, humility can be operationalized and measured along the dual dimensions of low self - focus and high other - focus and is distinct from other related constructs (e.g., modesty and open-mindedness). We discuss our newly developed scale (Study 1 and 2), and provide preliminary validation using self-report (Study 3) and behavioral measures (Study 4), showing that humility is related to people's general ethical orientation (e.g., empathy, universalism/benevolence, and civic responsibility), their well-being (e.g., sense of autonomy, life-purpose, and secure attachment), mature religious beliefs/practices, and reactions to disagreement – specifically, people high in humility sat closer and less angled away from their conversation partner with whom they disagreed. Together, this provides support for our new Dual-Dimension Humility Scale.